Evaluasi Keamanan Informasi Data Center Berdasarkan Standar ISO 27001:2013 (Studi Kasus PT. Pupuk Kalimantan Timur) - Faza Ainun Nafisah; Widhy Hayuhardhika Nugraha Putra; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Pupuk Kalimantan Timur is a company that meet the needs of fertilizer in Indonesia. PT. Pupuk Kalimantan Timur has a data center to manage a lot of important and valuable information which confidentiality must be maintained and secured with clear standards. According to Information Technology Decision and Security of PT. Pupuk Kalimantan Timur Number 357.A/D30000/V.18 2018, will perform an ISO 27001 certification on information security. Therefore, the purpose of this research is to evaluate the information security of data center using the SSE-CMM assessment index, to get the results of the Risk Priority Number (RPN) to assess the risk using FMEA and provide recommendations based on ISO 27001 standards. The results show the level of maturity of information security data center using SSE-CMM assessment index is at level 3 (define process). While the results of the risk assessment of data center assets using the FMEA method, there are 14 risks in the Very Low category, 2 risks in the Low category, and 2 risks in the High category. Overall PT. Pupuk Kalimantan Timur is declared feasible enough to conduct ISO 27001 certification. One improvement recommendation is to make WI to update the information security policy regularly and review the informatioisecurity policy.